Diplomacy as controversies - a study of the materialisation of the Nordic embassy complex in Berlin - Falkenberg, F (2020)
Diplomacy constitutes one of the most important fields of study within International Relations (IR). While significant process has been made to understand how diplomacy operates, scant attention has been devoted to understand creativity and materiality within diplomatic practice. This thesis aims to remedy this lacuna by developing a framework for studying diplomacy as controversies. The structure of the paper is as follows. To place the paper in context, I start by reviewing the existing literature, arguing that it provides a poor toolkit for capturing creativity and materiality. I then outline a methodological framework better equipped for this purpose. Applying a critical understanding of methods, I develop a two-layered approach, which consists of (1) setting the methodological ‘scene’ and (2) identifying methodological ‘tools’. This allows me to establish a robust link between the ‘processing’ and ‘gathering’ of data. Having sketched out the methodological framework, I then move onto the main body of the thesis. The thesis will be structured into three chapters. The first chapter develops a framework for studying ‘diplomatic controversies’. Drawing upon a wide range of literature, it shows how the study of controversies can give valuable insights into understandings of diplomacy. The second chapter explores how the study of controversies can help us rethink Nordic diplomatic practices by drawing on a case study concerning the establishment of the Nordic embassy complex in Berlin. The third chapter delves further into this by exploring how the materialisation of the Nordic embassy complex can allow us to rethink concepts within IR: the Nordics, creativity and materiality.